Hacia una revaloración ontológica del tridimensionalismo iusfilosófico como respuesta a los grandes retos del derecho actual. Estado del arte. (2007)
A brief glance at the panorama of actual post-positivist philosophy of Law, characterized by theacknowledgement of a three -elementary structure (factical-axiological-normative), with the purposeof understanding the appearance of Specific Jusphilosophical Tridimensionalism and its possibilities asan integrative theory will allow, with the reading of authors commited to a post-metaphysical and linguistic turn philosophy, the rescue of the Being as the axis of Law, and the fundamentals for a philosophy of Law, able to confront the challenges established by the new scientific and technological advances in matters of bioethics and communication and information mass-media.